1998
DOI: 10.1183/09031936.98.11061319
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmental tobacco smoke on cough in children with a history of tonsillectomy or adenoidectomy

Abstract: We examined the possible impact of tonsillectomy or adenoidectomy (T/A) on the relationship between environmental tobacco smoke (ETS) exposure and respiratory outcomes. This study was conducted in Humboldt, Saskatchewan, in 1993. The target population included all residents aged 6-17 yrs. Of the 1,019 eligible subjects, 892 participated (88%). Estimates of ETS exposure were based on the reported smoking habits of the children's household members. We defined current cough as a positive response to the question:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Despite the difficulties of separating the detrimental effects of maternal smoking before and after birth, a number of studies strongly suggest that passive smoke exposure after birth is harmful to children's lungs. For example, independent effects of paternal smoking on the incidence of respiratory disease in children have been demonstrated in countries such as China, where smoking rates are much higher among fathers than mothers 36–38 . Although the potential impact of passive smoke exposure during pregnancy on foetal lung development must be borne in mind when interpreting these results, the likelihood that postnatal exposure contributes to observed associations between parental smoking and respiratory problems in childhood is supported by the observations of a dose–response relationship with exposure, and a protective effect of day care 39 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the difficulties of separating the detrimental effects of maternal smoking before and after birth, a number of studies strongly suggest that passive smoke exposure after birth is harmful to children's lungs. For example, independent effects of paternal smoking on the incidence of respiratory disease in children have been demonstrated in countries such as China, where smoking rates are much higher among fathers than mothers 36–38 . Although the potential impact of passive smoke exposure during pregnancy on foetal lung development must be borne in mind when interpreting these results, the likelihood that postnatal exposure contributes to observed associations between parental smoking and respiratory problems in childhood is supported by the observations of a dose–response relationship with exposure, and a protective effect of day care 39 .…”
Section: Introductionmentioning
confidence: 99%
“…The impact of ETS on this patient group was complicated by the confounding associated with ETS being a cause of delayed surgical recovery and a cause of primary disease or recurrence. In five studies, 29 31–33 38 ETS exposure was treated as a confounding variable, rather than the primary focus of the study.…”
Section: Resultsmentioning
confidence: 99%
“…ETS exposure was usually measured as a binary exposed/unexposed variable, although additional measures such as identifying which family members smoked, 17 20 levels of smoking 29 and biological markers 14 23 were also used. One study showed good correlation between parental questioning and urinary cotinine levels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations